Implementation of Full-Featured PID Regulator in Microcontrollers - Krejcar, O.; Spicka, I.; Frischer, R. (Elektronika ir Elektrotechnika, 2011)
The goal of article is to provide a basic mathematical description of incremental controller and suggest structure of single blocks sothat be able to implement into single chip microcontroller. Individual blocks are analyzed as far as elementary operation’s level. Fromhardware description resulting, that selected structure is suitable for implement into similar MCU especially if they are able to conFig.I/O pins as with ours MCU. The article attends to the implementation of a full PID controller in the selected microprocessor. In orderthat PID controller met all demands of the modern control systems, it must include more than just the basic PID algorithm. Especiallynecessary is to implement treatment changes of the desired value by checking of its gradient. It should also be addressed treatment changes of action variable. There can be two ways how to do that: (a) limitations of the action control variable onto the allowable interval and treatment of the permissible gradient of the action variable, (b) establish direct forward coupling for the implementation of cascade control. For many applications it is necessary to allow the controller has to be able to switch from automatic to manual mode and vice versa bumpless. Splitting of the regulator into main blocks further can enable minimized time demands of the algorithm and to limit negative effects when input changes occur. A suitable controller design methodology as a reentrant routine and defining memory areas, then save processors program memory. The proposal is based on the PID model created in the MATLAB simulation environment. Ill. 10, bibl. 11 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.113.7.617